Traditional Institutions and Conflict Resolution in Contemporary Africa - Oladipo , Ileola Elizabeth (African Journal of Stability and Development (AJSD), 2022)
The failure of post-colonial African states in providing solutions to the incessant crises confronting them has been traced to their detachment from their institutional and cultural values. The argument is that modern techniques at resolving internecine conflicts in the continent have not yielded optimal results over the years. Whereas, in traditional African societies, the mechanism put in place to address conflicts prevented the atrophying of the communities and occasioned activities that promoted peace among members of the societies. Traditional Africa’s approaches to conflict resolution are believed to be largely guided by unique norms, values, as well as cultural and traditional settings of the community. These promoted their capacity to co-exist peacefully, to commune together, to respect one another, to forgive and to reconcile. In order to see how these can be replicated in contemporary Africa, research efforts have been dedicated to proffering alternative models that are contextually based, and more suitable for African societies. Therefore, in contribution to the volume of research in this area, this paper examines the indigenous institutions of conflict resolution in traditional African societies using the Yoruba societies as reference points. Specifically focussing on Ipetu-ljesa community in Oriade Local Government area of Osun State, Nigeria, the paper x-rays the role of the indigenous institutions of conflict resolution in Africa, the challenges they face in contemporary times as well as possible ways of engaging this model for conflict resolution in African societies.